2008
DOI: 10.1111/j.1365-2095.2007.00509.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of canola meal on physiological and biochemical parameters in rainbow trout (Oncorhynchus mykiss)

Abstract: Rainbow trout (initial body weight 4.16 ± 0.25 g) were fed diets [crude protein 420 g kg )1 ; gross energy 18.7 MJ kg )1 dry matter (DM); crude fat 110 g kg )1 ] containing graded levels of either a canola meal (crude protein 350 g kg )1 DM) supplemented with DL-methionine as partial fish meal protein. A growth trial was conducted over 16 weeks at a water temperature of 12 ± 1°C. At the end of the growth trial, in addition to body composition analyses, plasma tri-iodothyronine (T 3 ) and thyroxine (T 4 ), chol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
39
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 65 publications
(46 citation statements)
references
References 50 publications
(144 reference statements)
6
39
0
1
Order By: Relevance
“…The results of Shafaeipour et al (2008) suggest that the combined use of soybean meal and canola meal might help to overcome the limitations imposed by the singular use of the respective ingredients; Shafaeipour et al (2008) demonstrated that a diet containing 30% solvent-extracted canola meal and 24.4% soybean meal could be used in rainbow trout diets without affecting growth rate and nutrient utilization. The present study confirms that high-level mixtures of these ingredients can be utilized in rainbow trout diets.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The results of Shafaeipour et al (2008) suggest that the combined use of soybean meal and canola meal might help to overcome the limitations imposed by the singular use of the respective ingredients; Shafaeipour et al (2008) demonstrated that a diet containing 30% solvent-extracted canola meal and 24.4% soybean meal could be used in rainbow trout diets without affecting growth rate and nutrient utilization. The present study confirms that high-level mixtures of these ingredients can be utilized in rainbow trout diets.…”
Section: Discussionmentioning
confidence: 95%
“…Soybean and canola meals are used as primary plant protein sources in fish feeds owing to their relatively high crude protein level, high protein availability and complimentary amino acid composition compared with other oilseed meals (Hertrampf and Piedad-Pascual 2000;Lee et al 2002Lee et al , 2006. Many researchers have examined the efficacy of fish meal substitution in aquafeeds with a variety of oilseed meals at different levels of inclusion for a range of fish including rainbow trout (soybean meal: Refstie et al 1997Refstie et al , 2000Barrows et al 2007; cottonseed meal : Luo et al 2006; canola products: Drew et al 2007;Shafaeipour et al 2008). It has been demonstrated that soybean products (Rumsey et al 1994) and canola meal (Shafaeipour et al 2008) can be used to replace up to 30% of fish meal in rainbow trout diets without reducing growth performance.…”
Section: Introductionmentioning
confidence: 99%
“…In several fish-feeding trials, rapeseed products have been found to be viable alternatives to fish meal (Davies et al 1990;Burel et al 2000aBurel et al , b, c, 2001Thiessen et al 2003Thiessen et al , 2004Shafaeipour et al 2008). However, when replacing relatively high percentages of dietary fish meal, it was found that antinutritional factors present in rapeseed products such as glucosinolates, phytic acid or polysaccharides can negatively affect feed taste, feed intake and nutrient absorption and consequently deplete fish growth (Francis et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…In search of fish meal alternatives in aqua feeds, rapeseed (including canola) products have been widely tested as protein sources in diets for several fish species, among them rainbow trout Oncorhynchus mykiss (Stickney et al 1996;Burel et al 2001;Thiessen et al 2003Thiessen et al , 2004Shafaeipour et al 2008), tilapia Oreochromis niloticus (Davies et al 1990), wels catfish Silurus glanis (Slawski et al 2011b) and turbot Psetta maxima (Burel et al 2000a, c).…”
Section: Introductionmentioning
confidence: 99%
“…Dietas com a inclusão de 1.000 e 2.000 unidades de fitase ativa apresentaram melhor digestibilidade da proteína e disponibildiade do fósforo e consequentemente promoveram um melhor desempenho e maior deposição de cálcio e magnésio no tecido ósseo e escamas de juvenis de tilápia do Nilo (PORTZ; LIEBERT, 2004 , 1997;KIKUCHI, 1999;SOARES et al, 2000;FURUYA et al, 2001;GALDIOLI et al, 2002;AI et al, 2006;HELLAND;GRISDALE-HELLAND, 2006;DE FRANCESCO et al, 2007;GLENCROSS;BOOTH;ALLAN, 2007;HANSEN et al, 2007a;OLSEN et al, 2007;HU et al, 2008;SHAFAEIPOUR et al, 2008;ZHANG, et al, 2008). • Peso inicial (PI);…”
Section: Farelo De Sojaunclassified